Juvenile Amyotrophic Lateral Sclerosis: a mini review of literature (Journal of Medical Science, 2024)
Juvenile Amyotrophic Lateral Sclerosis (JALS) is a rare type of motor neuron disease that typically manifests before the age of 25. Research findings indicate that the most prevalent gene mutations linked to JALS are FUS, SETX, SIGMAR1, SPG11 and ALS2. In instances of familial occurrence, the gene mutations are predominantly inherited in an autosomal recessive manner, whereas mutations in SETX follow an autosomal dominant inheritance pattern. The clinical manifestations of JALS encompass a combination of upper and lower motor neuron degeneration, and the disease’s prognosis can range from rapidly progressive to a more gradual course. Specific gene mutations may give rise to distinct clinical features in addition to the fundamental motor neuron symptoms. Accurate diagnosis of JALS necessitates thorough clinical evaluation and genetic testing, as understanding the hereditary patterns and accompanying characteristics can offer valuable prognostic insights. Timely identification and proper management of JALS are imperative due to its rarity and significant impact on affected individuals.